Combined effects of runoff increase and sea level rise on the water exchange and saltwater intrusion for an estuary bay in non‐flood season. Issue 12 (1st December 2022) - He, Wei; Zhou, Hongxing; Zhang, Jian; Xu, Hui; Liu, Chunsheng
Abstract: Estuary bays are vulnerable to salinization effects due to relative sea level rise and modification in upland hydrology owing to a variety of factors. Much research has evaluated the one‐sided effect of runoff discharge or sea level on the water exchange and saltwater intrusion for an estuary, while their combined effects have not been evaluated, especially for an estuary bay with narrow river mouth. Taking the Wanquan Estuary Bay (WEB), China, as study case, this paper has revealed the long‐term significant increasing trend of freshwater runoff in non‐flood season during years 1956–2017 using the Man‐Kendall trend analysis, robust principle component regression and Theil–Sen's estimator. A 3‐D hydrodynamic‐salinity‐tracer numerical model is built and calibrated based on the finite‐volume community ocean model, and the effects of runoff increase and sea level rise on the water exchange and saltwater intrusion are investigated. This paper shows the following: (1) The freshwater runoff during non‐flood season in WEB shows significant long‐term increasing trend, and the mean changing magnitude is 0.4546 m 3 /s/a. (2) The increased runoff accelerates the water exchange, and reduces the turn‐over time and saltwater intrusion in the WEB. The sea level rise reduces the water exchange and increase the saltwater intrusion. (3) For the estuary bay with narrow river mouth, the salinity distributions show more vertical stratification characteristics. The freshwater runoff has power relationships with the average turnover time and salinity, and the sea level has linear relationships. (4) The water exchange and salinity of an estuary bay is more vulnerable to the changed runoff than the sea level rise, while the impacts of sea level rise would increase for estuaries with wide river mouth. This paper provides support for the freshwater exploitation and utilization in estuary bay under the background of climate change and sea level rise. Abstract : Focusing on an estuary bay, the long‐term change of fresh runoff was analyzed. Based on a 3‐D hydrodynamic‐salinity‐tracer model using FVCOM, the effects of runoff increase and sea level rise on the water exchange and saltwater intrusion for an estuary bay were revealed.